Modeling and Simulation of Photovoltaic Module with MPPT - Wan Muhammad Firdaus, Wan Sulaiman; Hamdan, Daniyal (2013)

(untitled)
This paper presents modeling and simulation of a photovoltaic (PV) module employs with maximum power point tracker (MPPT) used as a learning device in Universiti Malaysia Pahang (UMP). This model is based on mathematical equations and is described through an equivalent circuit including a photocurrent source, a diode, a series resistor and a shunt resistor. The modelling, simulations and MPPT algorithm of the system will be modeled and simulated using MATLAB script using actual irradiance data. Simulation results will be presented in term of comparisons of the PV module characteristics between the manufacturers graph and MATLAB model and also its performance such as total output power produced between the sunniest and cloudiest day using perturb & observe (P&O) method